Enhancing Students’ Vocabulary through Authentic Materials and Multimedia - Marpaung, Marlin Steffi; Situmeang, Hardi Jhon Pinondang (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2020)
Vocabulary is the fundamental aspect in learning English. Without adequate vocabulary learners find it difficult to communicate, express ideas or opinion, comprehend simple text, and listen to instruction. Authentic materials refers to pictures, photographs, video selection and radio. This study sought to find out the following questions: How is the vocabulary ability of students who were taught using authentic materials through multimedia and authentic materials only? Is the vocabulary enhancement of those students who are taught using authentic materials through multimedia is better than those students who are taught using authentic materials? What are the students’ responses toward the use of authentic materials and multimedia? The study was quantitative research method and a comparative design by using pre-test and post-test. The populations of this study were 10th grade of senior high school students where they are divided into two groups, the first group were taught using authentic materials through multimedia and the second group were taught using authentic materials. The instruments used in this study were vocabulary test and questionnaire. The result of this study showed that both groups has enhanced the vocabulary ability with the mean score of pre-test was 53.93 for authentic materials through multimedia and 59.97 for authentic materials. It indicated that the initial ability of the authentic materials group was higher than the authentic materials through multimedia group. Therefore, the mean score of the post-test was 73.80 for the authentic materials through multimedia group and 70.83 for the authentic materials group. It showed that the result of the authentic materials through multimedia group was better than the authentic materials group. The students’ responses toward the use of authentic materials through multimedia were 80% positive and only 3,3% positive response towards the use of authentic materials. The conclusion of this study is the use of authentic materials through multimedia is very effective to enhance students’ vocabulary knowledge. Furthermore, suggestion for the English teachers, it is recommended to use authentic materials through multimedia to teach and enhance students’ vocabulary knowledge. It is very effective technique to be applied at the classroom and to make the students engage on the teaching and learning process. Meanwhile, teachers need to prepare the material needed ahead since it is time consuming and ensure the school has provided enough facility especially computers, projector and internet access to support the learning process.